Стан правового захисту журналістів в Україні - Теребус, Роман М.; Terebus, R. М. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Автор, аналізуючи сучасний стан правових відносин між журналістами та суспільством, намагається знайти причини порушення прав журналістів під час виконання їх професійних обов’язків. Журналісти, збираючи інформацію, наштовхуються на супротив і тиск із боку можновладців. Існує політична цензура, окремі положення чинних законів застаріли або містять певні неузгодженості. By analyzing the current state of legal relations between journalists and the society, the author tries to find causes of violations of journalists' rights while they are performing their professional duties.Mass media shape people’s opinions and views, as well as ensuring that politicians, managers, enforcement bodies perform their duties in a diligent way and do not violate the legislation. However, while gathering information, journalists faceopposition and pressure from the authorities. There existspolitical censorship, certain provisions of the existing laws are outdated or inconsistent.In the today's context, despite regulationsof domestic and international laws, mass media have some problems associated with realization of the journalistic freedom and right to information. There is a dangerous situation in Ukraine with ensuring fundamental rights and freedoms of citizens to receive complete andunprejudiced information and ensuring rights of journalists for a free performance of their professional duties without any external pressure.
State of Legal Protection of Journalists in Ukraine
Keywords: закони України; Ukraine’s laws; права журналістів; journalists' rights; професійна діяльність журналістів; professional activities of journalists; тиск на ЗМІ; pressure on the media; політична цензура; political censorship